PEMERATAAN DAN KEADILAN EKONOMI DI INDONESIA (PERSPEKTIF EKONOMI SYARIAH) - Amin, Darwis (AMAL: Jurnal Ekonomi Syariah, 2023)
AbstractsThis study aims to understand the equitable distribution of the economy in Indonesia and to look at the Islamic economic perspective on economic justice in the context of economic equality in Indonesia. This type of research is library research with analysis tools using the Gini coefficient, Theil index, L index and the World Bank. The results of the study show (1) There is still inequality in the distribution of the economy in Indonesia because there is a significant increase in the wealth of capital owners, while workers only have capital in the form of labor and skills. (2) In the context of economic equality in Indonesia, the Islamic perspective puts forward the concept of economic distribution that covers the entire Indonesian economic system with the principle of economic justice according to Islamic teachings.Keyword: economic equity, economic justice, gini ratio, Theil index, L index AbstrakPenelitian ini bertujuan untuk memahami distribusi ekonomi yang merata di Indonesia serta melihat perspektif ekonomi Islam mengenai keadilan ekonomi dalam konteks pemerataan ekonomi di Indonesia. Jenis penelitian merupakan penelitian kepustakaan dengan alat analisis menggunakan koefisien gini, indeks Theil, indeks L serta Bank Dunia. Hasil penelitian menunjukkan (1) Masih terjadi ketimpangan dalam pendistribusian ekonomi di Indonesia karena terdapat peningkatan yang signifikan dalam kekayaan pemilik modal, sedangkan pekerja hanya memiliki modal berupa tenaga kerja dan keterampilan. (2) Dalam konteks pemerataan ekonomi di Indonesia, perspektif Islam mengemukakan konsep distribusi ekonomi yang mencakup seluruh sistem ekonomi Indonesia dengan prinsip keadilan ekonomi menurut ajaran Islam.Kata Kunci: pemeratakaan ekonomi, keadilan ekonomi, gini rasio, indeks Theil, indeks L